Studies on Leaf Venation in Selected Taxa of the Genus Ficus L. (Moraceae) in Peninsular Malaysia - Ummu Hani Badron; Noraini Talip; Abdul Latiff Mohamad; Affina Eliya Aznal Affenddi; Amirul Aiman Ahmad Juhari (Tropical Life Sciences Research, 2014)
A study on the variation of leaf venation patterns was conducted on 21 taxa of the genus Ficus in Peninsular Malaysia. The results showed the existence of eight leaf venation patterns based on veinlets, the ultimate marginal and areolar venation. The majority of species, such as F. annulata, F. benghalensis, F. benjamina, F. deltoidea var. angustifolia, F. deltoidea var. kunstleri, F. depressa, F. elastica, F. hispida, F. microcarpa, F. religiosa, F. tinctoria, F. ucinata and F. vasculosa, show tri-veinlets. The others exhibit the following: bi-veinlets in F. aurata and F. heteropleura; uni-veinlets in F. lepicarpa, F. schwarzii and F. superba; and simple veinlets in F. aurantiacea and F. fulva. F. sagittata presents no veinlets for areolar venation. The presence of tracheid or swollen veins at the centre of the lamina and the presence of cystolith cells and trichomes are common anatomical characteristics that could assist in group classification of the studied species. Variations in leaf venation patterns are not only valuable in identifying a taxon group, but can also be used to differentiate between species in the genus Ficus. Kajian variasi corak peruratan daun telah dijalankan terhadap 21 takson daripada genus Ficus di Semenanjung Malaysia. Hasil menunjukkan kehadiran lapan corak peruratan daun berdasarkan percabangan urat, peruratan tepi dan tengah lamina daun. Majoriti spesies seperti F. annulata, F. benghalensis, F. benjamina, F. deltoidea var. angustifolia, F. deltoidea var. kunstleri, F. depressa, F. elastica, F. hispida, F. microcarpa, F. religiosa, F. tinctoria, F. ucinata dan F. vasculosa menunjukkan urat bercabang tiga. Corak lain hadir seperti berikut: urat bercabang dua pada F. aurata dan F. heteropleura; urat bercabang satu pada F. lepicarpa, F. schwarzii dan F. superba; dan urat ringkas pada F. aurantiacea dan F. fulva. F. sagittata menunjukkan tiada percabangan yang hadir untuk tengah lamina. Kehadiran trakeid atau urat membengkak pada bahagian tengah lamina dan kehadiran sel sistolit serta trikom merupakan ciri anatomi sepunya yang boleh membantu dalam pengkelasan kumpulan spesies kajian. Variasi corak peruratan daun bukan sahaja mempunyai nilai dalam mengenal pasti kumpulan takson, malah boleh juga digunakan untuk membezakan antara spesies dalam genus Ficus.